1984
DOI: 10.1073/pnas.81.12.3883
|View full text |Cite
|
Sign up to set email alerts
|

Modification of low density lipoprotein by endothelial cells involves lipid peroxidation and degradation of low density lipoprotein phospholipids.

Abstract: Low density lipoprotein (LDL) incubated with cultured endothelial cells from rabbit aorta or human umbilical vein is altered in several ways (EC-modified): (i) It is degraded by macrophages much faster than LDL similarly incubated in the absence of cells or incubated with fibroblasts.(ii) Its electrophoretic mobility is increased. (iii) Its density is increased. We report here that antioxidants completely prevent these changes. We also report that these changes do not take place if transition metals in the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
761
0
14

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,448 publications
(792 citation statements)
references
References 23 publications
17
761
0
14
Order By: Relevance
“…Abbreviations: BCDS, bathocuproine disulphonic acid; DMPO,5, EPR, electron paramagnetic resonance; 13-HPODE, 13(S)-hydroperoxyoctadeca-9Z,11E-dienoic acid 2…”
Section: Subject Area: Systems Biochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations: BCDS, bathocuproine disulphonic acid; DMPO,5, EPR, electron paramagnetic resonance; 13-HPODE, 13(S)-hydroperoxyoctadeca-9Z,11E-dienoic acid 2…”
Section: Subject Area: Systems Biochemistrymentioning
confidence: 99%
“…A number of large clinical trials have shown no decrease in cardiovascular disease after antioxidant supplementation, however, and the importance of oxidised LDL in atherosclerosis is therefore an unresolved issue [2]. Several studies have demonstrated that LDL can be oxidised in vitro by cells associated with atherosclerotic lesions [3][4][5][6][7]. The mechanisms of LDL oxidation in vivo are controversial [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most workers find that LDL oxidation by cells requires the presence of transition metal ions, usually iron [7,9], but copper ions will also catalyse the oxidation [9,10]. A sufficiently high concentration of iron [7,9] or copper [10,11] can catalyse the oxidation of LDL in the absence of cells.…”
Section: Reagentsmentioning
confidence: 99%
“…During the oxidation process, a number of chemical changes take place within the lipoprotein particle, including an increase in density, a decrease in content of esterified cholesterol, fragmentation of apolipoprotein B and an increase in negative charge, leading to increased electrophoretic mobility [1][2][3]. As a consequence, oxLDL are no longer recognized by the native LDL receptor, but instead interaction with the so-called scavenger receptor is induced.…”
Section: Introductionmentioning
confidence: 99%